EDITORIAL - Ordonez, J. C. (Revista de Engenharia Térmica, 2014)
I would like to direct the attention of the reader to Second Law of thermodynamics approaches to the control and optimization of dynamic energy systems. Second Law approaches to optimization and control have emerged as an enhancement beyond First Law efforts. Second Law-based metrics have the inherent advantage of being applicable to a wide variety of systems under a variety of physical phenomena (e.g., heat transfer, fluid flow, electromagnetic effects, radiation). Exergy and Second Law efficiencies have been utilized as metrics in optimization of energy systems and in the formulation of control schemes, however, most efforts have emphasized on steady-state systems and have addressed mainly operational parameters (e.g., flow rates, pressure and operating temperature levels). Second Law based metrics are expected to be useful not only for operational studies, but more importantly in leading to the discovery of optimal system configurations. Dynamic models in conjunction with Second Law metrics can lead to the optimization of important system design features beyond operational parameters.